Bats (Chiroptera) from the premontane forest of San Ramón, Costa Rica - Zamora Mejías, Daniel (2017)
Biological monitoring is the best way to assess the status of populations from a set of organisms in an environment and quantifies its richness, abundance and diversity through its range of distribution. In total, 216 bats were captured using mist nets, and was determined the presence of three bat families (Phyllostomidae, Mormoopidae and Vespertilionidae), 22 genera and 40 species. The family Phyllostomidae was the most diverse (32 species) and abundant (190 individuals). Additionally, we present the record of six species reported in other independent investigations. The 46 species of bats reported here for the premontane forest of San Ramon, Alajuela, represents 40% of the bat species reported in Costa Rica.